2018
DOI: 10.1136/bjophthalmol-2017-311831
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and myopia progression in Chinese children: the Anyang Childhood Eye Study

Abstract: In this sample of Chinese children, myopia progression over 2 years was inversely related to IOP, suggesting that IOP had essentially no relationship with myopia progression in school children. The lower IOP in progressing myopic eyes may indicate more compliant sclerae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 33 publications
4
20
0
Order By: Relevance
“…For students with unaided visual acuity 0.3 or worse in either eye, subjective refraction was performed to obtain best-corrected visual acuity by trained optometrists. The cycloplegic procedure referred to the Anyang Childhood Eye Study [10]. Cycloplegia was achieved with two drops of 1% cyclopentolate and 1 drop of Mydrin P at a 5-min interval.…”
Section: Distant Visual Acuitymentioning
confidence: 99%
“…For students with unaided visual acuity 0.3 or worse in either eye, subjective refraction was performed to obtain best-corrected visual acuity by trained optometrists. The cycloplegic procedure referred to the Anyang Childhood Eye Study [10]. Cycloplegia was achieved with two drops of 1% cyclopentolate and 1 drop of Mydrin P at a 5-min interval.…”
Section: Distant Visual Acuitymentioning
confidence: 99%
“…However, in progressive high myopia, especially pathologic myopia, it has been reported that the sclera of these patients was continually prolonged and had higher compliance and, consequently, was more elastic and more sensitive to IOP change. 37 , 51 In summary, we hold the view that lowering the IOP can slow down AL increase, especially in progressive high myopia populations.…”
Section: Evaluations In Clinical Practicesmentioning
confidence: 83%
“…However, in eyes with greater myopia progression, IOP was significantly lower, which indicated that progressing myopic eyes have higher scleral compliance. 37 A multivariate linear regression analysis used in the Anyang University Students Eye Study described that higher IOP is associated with higher myopic refractive error and shorter AL. As the sclera has a certain compliance, below the threshold, the correlation between IOP and AL was negative, while above a certain degree, the correlation was positive.…”
Section: Evaluations In Clinical Practicesmentioning
confidence: 99%
“… 10 , 11 In contrast, others showed an inverse association between IOP and myopia. 12 , 13 We speculate that the inconsistencies in the results occur from the fact that IOP is an influencing factor of ocular perfusion pressure but cannot represent ocular tissue perfusion. 9 …”
Section: Introductionmentioning
confidence: 95%